Salmonella gallinarum strains from outbreaks of fowl typhoid fever in Southern Africa closely related to SG9R vaccines - Beylefeld, Amanda; Abolnik, Celia (Frontiers in Veterinary Science, 2023)
Salmonella enterica subspecies enterica serovar Gallinarum biovar Gallinarum (SG) is associated with Fowl Typhoid Fever and the attenuated rough strain SG9R is widely used as a vaccine in many regions. Reversion to virulence of vaccine strains was suspected as the cause during recent fowl typhoid fever outbreaks in poultry in South Africa and Eswatini. Whole genome comparison with single nucleotide polymorphism (SNP) detection was used to compare nine field isolates with global wild-type SG9 strains and the two commercial SG9R vaccines in use, Nobilis® SG9R and Cevac®-SG. SNP phylogenic analysis showed that all the southern African field isolates were more closely related to the vaccine strains than wild-type SG9 strains. Furthermore, SNPs in the pyruvate dehydrogenase (aceE) and/or lipopolysaccharide 1.2-glucosyltransferase (rfaJ) genes, that are known markers of attenuation, were found in four of the field isolates along with intact spv, SPI-1 and SPI-2 gene clusters, providing conclusive evidence that these four isolates were originally vaccine strains that reverted to virulence. Five other field isolates lacked the characteristic markers of attenuation of SG9R, but variant analysis identified a SNP in the yihX gene, insertions in the ybjX and hydH genes as well as deletions in the ftsK and sadA genes that were shared between the field isolates and vaccine strains, but were absent from wild type SG9, and these field isolates were therefore also likely revertant vaccines. Overall, this study highlights different mechanisms of reversion of two commercial vaccines, where virulence caused by field isolates closely related to the Nobilis® SG9R vaccine was associated with the restoration of intact virulence gene clusters, and those derived from the Cevac®-SG vaccine were characterised by point mutations resulting in restored aceE and rfaJ genes. A possible new marker of attenuation was identified as a point mutation in the yihX gene, plus four new candidate genes that could potentially be used distinguish current vaccine strain from wild-type strains in PCR assays.